A Calculation Model of Cutterhead Resistance for Pipe Jacking in Rock Strata and Soil–Rock Composite Strata - Yulong Cao; Ran Zhong; Rongdong Tao; Feilun Luo; Liang Xiong; Yue Fan; Jiahao Mei; Peng Zhang (Engineering Reports)
ABSTRACT Jacking force is one of the most important parameters in the design and construction of pipe jacking engineering, and cutterhead resistance is an important part of jacking force. Pipe jacking is increasingly applied to rock strata, but there are few calculation models for the jacking force in rock strata and soil–rock strata. For this reason, this article, under the assumption of stable conditions of pipe jacking face, summarizes the cutterhead resistance of soil strata. The rock‐breaking mechanism, stress model, and influence law of cutterhead of rock pipe jacking machine are analyzed. And on this basis, the calculation formula of cutterhead resistance of pipe jacking in rock strata is deduced. And the cutterhead resistance of soil–rock composite strata is determined according to the proportion of strata. Finally, the field measured values and code calculation results are compared with the formula values in this article. The results show: in rock pipe jacking, the compressive and shear strengths of the rock and the depth of the pipe jacking cutter cut into the rock directly determine the value of the cutterhead resistance; and the calculated value of cutterhead resistance of soil–rock composite strata determined according to the strata ratio is consistent with the measured cutterhead resistance, which proves its applicability.